The association between serum adipokines levels with senile osteoporosis: a systematic review and meta-analysis - Wang, Jiangna; Liu, Shiwei; Zhao, Yuxiang; Naqvi, Syed Shah Zaman Haider; Duan, Ruixue (Frontiers in Endocrinology, 2023)
Objective: The clinical correlation between adipokines levels in the blood and the incidence of senile osteoporosis (SOP) has not been clearly studied. We conducted this meta-analysis to elucidate the relationship between three common adipokines levels (leptin, adiponectin, and chemerin) and the incidence of SOP. Methods: We searched databases such as CNKI, CBM, VIP, Wanfang, PubMed, Web of Science, Embase, and the Cochrane Library to collect articles published since the establishment of the database until July 30, 2022. Results: In total, 11 studies met the selection criteria. Our meta-analysis showed that serum leptin levels were significantly lower (mean difference [MD], -2.53, 95% CI: -3.96 to -1.10, I2 = 96%), chemerin levels were significantly higher (MD, 30.06, 95% CI: 16.71 to 43.40, I2 = 94%), and adiponectin levels were not significantly different (MD, -0.55, 95% CI: -2.26 to 1.17, P = 0.53, I2 = 98%) in SOP patients compared with healthy older individuals with normal bone mineral density (BMD). In addition, correlation analysis showed that leptin levels were positively correlated with lumbar bone mineral density (LBMD) (r = 0.36) and femoral bone mineral density (FBMD) (r = 0.38), chemerin levels were negatively correlated with LBMD (r = -0.55) and FBMD (r = -0.48), and there were significant positive correlations between leptin and adiponectin levels and body mass index (BMI) (r = 0.91 and 0.97). Conclusions: The likelihood of having SOP was higher in older individuals with low levels of leptin and higher levels of chemerin. In addition, BMI was somewhat lower with low levels of leptin and adiponectin.